Prinsip Kesalehan Sosial bagi Muda-Mudi Kristen di Ruang Media Sosial - Erman Sepniagus Saragih (Jurnal Teologi Gracia Deo, 2023)
The degradation of the habitat of the church’s youth generation and their increasing presentation in the social media space challenge the church to formulate principles of adaptive ministry. This study aims to describe the construction of the principle of social piety based on a constructive reading of the literature to argue for the principle of adaptive service for Christian youth. Some literature related to church service efforts on the impact of social media on Christian youth is always based on vertical spiritual relations. However, horizontal relationships are also significant, as is the principle of social piety. The method used is descriptive qualitative with a secondary data literature study approach. The conclusion is that social piety includes material about balancing faith and works, doing God’s will, loving others and being tolerant, and obeying the government. These four principles are very relevant to be stimulated young Christians in the context of diversity in Indonesia to maintain peace amid diversity. AbstrakDegradasi habitus generasi muda-mudi Kristen dan meningkatnya presentasi mereka dalam ruang media sosial menantang gereja berpikir untuk merekonstruksi prinsip pelayanan muda-mudi yang adaptif. Tujuan penelitian ini adalah mendeskripsikan konstruksi prinsip kesalehan sosial berdasarkan pembacaan literatur secara konstruktif untuk mengargumentasikan prinsip pelayanan adaptif bagi muda-mudi Kristen. Beberapa literatur terkait upaya pelayanan gereja terhadap dampak media sosial bagi muda-mudi Kristen selalu berbasis relasi spiritual vertikal adalah baik, akan tetapi relasi horizontal juga sangat penting sebagaimana prinsip kesalehan sosial. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi literatur data sekunder. Kesimpulannya adalah bahwa kesalehan sosial mencakup materi tentang keseimbangan antara iman dan perbuatan, melakukan kehendak Allah, mengasihi sesama dan toleran, dan patuh kepada pemerintah. Keempat prinsip tersebut sangat relevan distimulasikan bagi muda-mudi Kristen dalam konteks kebhinekaan di Indonesia untuk merawat perdamaian di tengah-tengah keberagaman.